Dynamic Grid Voltage-Based Impedance-Reshaped Control for the Stability Enhancement of Grid-Connected DC/AC Converter System under Bidirectional Power Flow - Li Liu; Kun Wang; Fei Peng; Yanjun Tian; Yi Wang (Energies, 2022)
Considering the bidirectional three-phase DC/AC converter, it presents different impedance characteristics on AC side under different power flow directions, resulting in different stability margin. This may cause the system instability at high-power level. This directionally oriented stability difference has not been paid enough attention in the grid-connected converter control. To mitigate the stability variations under bidirectional power flow, a dynamic grid voltage-based impedance reshaping control is proposed in this paper. The proposed method extracts the grid voltage dynamic component, and correspondingly compensates the power output, which is capable of regulating the power output coordinated with voltage dynamics in both power flow directions, neutralizing the stability difference and enhancing the bidirectional power flow stability. Unlike the conventional unidirectional damping optimization control in the current loop, the proposed control method can maintain satisfied stability under bidirectional power flow through the grid side voltage, which can avoid increasing the current loop delay, and thus endow the converter flexible bidirectional power process capability. The effectiveness of the proposed method has been verified by both simulations and experiments.